Análise do nível de pressão sonora dos condicionadores de ar das salas de aula da Ufersa/Caraúbas - Silva, Viviane Dutra da (Universidade Federal Rural do Semi-Árido, 2018)
When buying an air-conditioner, we often do not give the attention and care necessary to the appliance because it is not important to keep it running properly and this can change the operating form of the air conditioner, starting to function Incorrectly. Thus, it can bring us unexpected situations that can offer risks to the safety and health of those who attend the university and this can be avoided, therefore, the maintenance and prevention of the appliance are important. The noise analysis will tell us what the noise level of the UFERSA Block 1 classrooms students and UFERSA employees are being subjected to and can also show if air conditioners are presenting any operational defects, since noise is caused by a malfunction of the apparatus. Some rooms will be selected for noise analysis. Samples will be collected with the use of decibel, a noise meter. Through the results obtained from the noise meter, it will be possible to make an average and standard deviation so that a result can be obtained and thus compare with the standards of ABNT and the manufacturer's air conditioner manual.
Monografia
Keywords: Ar-condicionado; Ruído; Manutenção; Prevenção; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA